Metode Mengatasi Stress Kerja Di Lembaga Pendidikan Dalam Perspektif Islam - Latifah, Hafidah Dinatul; Fronica, Imelda; Asmendri, Asmendri; Sari, Milya (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This research aims to determine methods of dealing with stress in educational institutions from an Islamic perspective. Qualitative research methods are a type of research used, by searching for sources and drawing conclusions from these sources, such as books, journals and articles as well as from previous research. Based on research, it shows that in the world of work it is also known as work stress, which is a condition that affects a person's condition, there is a feeling of pressure on the mind, the influence of unstable emotions, disruption of thoughts and other conditions at that time. Factors that cause stress can arise from the individual, as well as the conditions surrounding/the individual's environment. A person must be able to control work stress on himself. In the Islamic view, work stress is a test from Allah SWT to test obedience and faith. The methods taught in Islam which are sourced from the Qur'an and hadith in dealing with stress are increasing faith and devotion to Allah SWT by increasing obligatory and sunnah worship, always being grateful to Allah, always being patient and sincere, maintaining good relations between each other/stay in touch and maintain physical health.